Incidental finding of inflammatory fibroid polyp of the appendix in a patient with acute appendicitis - M. Sy, Alexander; Vo, Duc; Friedel, David; Grendell, James; Hanna, Iman (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Sy AM, Vo D, Friedel D, Grendell J, Hanna I. Incidental finding of inflammatory fibroid polyp of the appendix in a patient with acute appendicitis. Turk J Gastroenterol 2020; 31(11): 831-34.